Retrospective Analysis of Perioperative Variables Associated With Postoperative Delirium and Other Adverse Outcomes in Older Patients After Spine Surgery. Issue 4 (October 2019) - Susano, Maria J.; Scheetz, Seth D.; Grasfield, Rachel H.; Cheung, Dominique; Xu, Xinling; Kang, James D.; Smith, Timothy R.; Lu, Yi; Groff, Michael W.; Chi, John H.; Crosby, Gregory; Culley, Deborah J.
Abstract : Background: The aim of this retrospective study was to identify perioperative variables predictive of the development of delirium in older surgical patients after spine surgery. Materials and Methods: We collected preoperative, intraoperative, and postoperative data on patients 65 years of age and above having spine surgery between July 1, 2015 and March 15, 2017. The primary outcome was the development of postoperative delirium. Data were analyzed using univariate and multivariable analysis. Results: Among the 716 patients included in this study 127 (18%) developed postoperative delirium. On multivariable analysis, independent predictors of postoperative delirium included older age (odds ratio [OR]=1.04; 95% confidence interval [CI], 1.00-1.09; P =0.048), American Society of Anesthesiologists physical status >2 (OR=1.89 [95% CI, 1.04-3.59]; P =0.042), metabolic equivalents of task <4 (OR=1.84 [95% CI, 1.10-3.07]; P =0.019), depression (OR=2.01 [95% CI, 1.21-3.32]; P =0.006), nonelective surgery (OR=4.81 [95% CI, 1.75-12.79]; P =0.002), invasive surgical procedures (OR=1.97 [95% CI, 1.10-3.69]; P =0.028) and higher mean pain scores on postoperative day 1 (OR=1.28 [95% CI, 1.11-1.48]; P <0.001). Conclusions: Postoperative delirium is a common complication in older patients after spine surgery, and there are several perioperative risk factors associated with its development. Abstract : Supplemental Digital Content is available in the text.